Work as a fator ofevasionaand return to EJA: an analysis of a group of Youth and Adult Education in Caruaru-PE - Viviane Rauane Bezerra Silva; Maria Fernanda dos Santos Alencar (Universidade Estadual de Alagoas, 2021)
This text addresses work as a relevant factor for the evasion and return of students who are now part of Youth and Adult Education (EJA). It aims to understand the interference of work for dropout and return to school in the EJA modality; having as an empirical field a school from the peripheryin the city of Caruaru, in 2019. We rely on the contributions of the authors (Gagno and Portela (2013); Cury (2000); Groppo (2000); Freire (1996); Ribeiro (2010) ); Arroyo (2006); Silva and Moura (2013); and Batalha e Silva (2018), to analyze and substantiate all of our research, where it has a qualitative character, conducting semi-structured interviews with 14 EJA students from elementary school -final years, using Content Analysis for the analysis of the interviews.The results of the survey showed that10 students: 5 men and 5 women left and returned to studies because of the early need for work; 4 women said they had left school due to the early pregnancy, but they returned returning to complete their studies and enter the job market. In this sense, weobserved that the same factor -work, which causes school dropout is also responsible for returning to school. new working conditions, wages and better living conditions and a continuity of studies aiming, for women, professionalization.